Role of TiO2 Nanoparticles in Wet Friction and Wear Properties of PEO Coatings Developed on Pure Titanium - Maryam Molaei; Arash Fattah-Alhosseini; Meisam Nouri; Mosab Kaseem (Metals, 2023)
The present study aims to explain how the incorporation of anatase TiO2 nanoparticles at three different concentrations, i.e., 1, 3, and 5 g/L, into the ceramic-like oxide plasma electrolytic oxidation (PEO) coatings on pure titanium substrate can affect the friction and wear behavior of the coatings in simulated body fluid (SBF) aqueous solution. For this purpose, a ball-on-disk friction and wear tester was utilized to characterize the wear performance of the PEO coatings. The morphology and dimensions (width and depth) of wear tracks were analyzed by scanning electron microscopy (SEM) and 2D depth profilometry, respectively. The results indicated that abrasive wear was identified in all PEO coatings; however, the coefficient of friction (COF), wear volume loss, and wear rate were strongly affected by the concentration of TiO2 nanoparticles. The coatings containing TiO2 nanoparticles presented a lower COF, less wear volume loss, reduced wear rate, and improved wear resistance due to having smoother surfaces and the presence of hard TiO2 nanoparticles on their surfaces and inside the pores. The coating with 3 g/L of TiO2 nanoparticles demonstrated the lowest wear rate value of 1.33 × 10−6 mm3/Nm (about a 32% reduction compared with that of coating without TiO2 nanoparticles) and the best wear protection properties among all coatings under investigation. The findings suggest TiO2 nanoparticles incorporated PEO coatings as a promising choice of surface treatment wherein the load-bearing capacity of titanium implants is critical.